Efficacy of the doktormitSDM training module in supporting shared decision making − Results from a multicenter double-blind randomized controlled trial. Issue 12 (December 2017) - Geiger, Friedemann; Liethmann, Katrin; Reitz, Daniela; Galalae, Razvan; Kasper, Jürgen
Highlights: DoktormitSDM is a compact training module to support shared decision making by physicians of any specialty. It was evaluated in a multicenter double-blind randomized controlled trial. The primary endpoint SDMmass incorporates the views of patient, physician and observer. The training module proved to be effective and efficient. It is ready for large-scale implementation. Abstract: Objective: Training to improve physicians' shared decision making (SDM) competencies with proven effectiveness and efficiency is rare. This study evaluated the brief in situ training module 'doktormitSDM'. Methods: In a multicenter RCT, each physician recorded four consultations, each of which included a diagnostic or treatment decision (N = 152 consultations from seven medical specialties). The doktormitSDM training module included two video-based individual coaching sessions (15 min) at the physicians' workplaces, supplemented by a manual and a video tutorial. Primary endpoint was the compound measure SDMmass (based on the MAPPIN'SDM system) which incorporates patient and observer perceptions of involvement and doctor-patient concordance on perceived involvement. Results: SDMmass increased significantly in the intervention group compared to the controls (effect size 0.58; p= 0.05; t -test). This effect tended to persist at follow-up (effect size 0.63; p=0.06). Patients' perceived involvement increased accordingly (effect sizes 0.9/.58; p=0.01/.07). Conclusion: The doktormitSDM training module is effective and efficient at improving SDM competencies. This is the first SDM training to be evaluated with a compound measure simultaneously considering doctor, patient and observer ratings. Practice implications: Owing to its very brief form and its reference to the doctors' own consultation videos, the doktormitSDM training module meets clinicians' needs and time constraints.